Application of a Tetra‐TPD‐Type Hole‐Transporting Material Fused by a Tröger's Base Core in Perovskite Solar Cells. Issue 9 (2nd September 2019) - Braukyla, Titas; Xia, Rui; Malinauskas, Tadas; Daskeviciene, Maryte; Magomedov, Artiom; Kamarauskas, Egidijus; Jankauskas, Vygintas; Fei, Zhaofu; Roldán-Carmona, Cristina; Momblona, Cristina; Nazeeruddin, Mohammad Khaja; Dyson, Paul J.; et al.
Abstract : In article no.1900224, Mohammad Khaja Nazeeruddin, Paul J. Dyson, Vytautas Getautis, and co‐workers present a novel hole transporting material, termed V1160, based on four N, N′‐bis(3‐methylphenyl)‐N, N′‐diphenylbenzidine‐type fragments, fused by a Tröger's base core. The material is synthetically robust and demonstrates a promising power conversion efficiency of over 18%. Moreover, V1160‐based devices exhibit improved performances in dopant‐free configurations and superior stability.